2007
DOI: 10.1063/1.2727557
|View full text |Cite
|
Sign up to set email alerts
|

Direct and in vitro observation of growth hormone receptor molecules in A549 human lung epithelial cells by nanodiamond labeling

Abstract: This letter presents direct observation of growth hormone receptor in one single cancer cell using nanodiamond-growth hormone complex as a specific probe. The interaction of surface growth hormone receptor of A549 human lung epithelial cells with growth hormone was observed using nanodiamond’s unique spectroscopic signal via confocal Raman mapping. The growth hormone molecules were covalent conjugated to 100nm diameter carboxylated nanodiamonds, which can be recognized specifically by the growth hormone recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 22 publications
1
65
0
1
Order By: Relevance
“…Such cNDs, especially detonation NDs, have been functionalised with biomolecules through either adsorption by electrostatic and/or hydrophobic interactions [16][17][18][19] or covalent linkage. [16,[20][21][22] In a few reports, the activities and/or the intracellular locations of these conjugated NDs were analysed. [17,18,22] One of the most critical points that has limited the use of NDs in biological applications is the preparation of a functionalised cND colloidal suspension that is stable over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Such cNDs, especially detonation NDs, have been functionalised with biomolecules through either adsorption by electrostatic and/or hydrophobic interactions [16][17][18][19] or covalent linkage. [16,[20][21][22] In a few reports, the activities and/or the intracellular locations of these conjugated NDs were analysed. [17,18,22] One of the most critical points that has limited the use of NDs in biological applications is the preparation of a functionalised cND colloidal suspension that is stable over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Weng et al (2009) found that transferrin-conjugated 100-nm diamonds were taken up via the abundant transferrin receptors on HeLa cells in a clathrin-dependant manner. In contrast, Cheng et al (2007) observed that similar-sized nanodiamonds conjugated to growth hormone remained extracellular, presumably attached to the binding domain of the growth hormone receptor on A549 cells, while the unconjugated control nanodiamonds were internalised. Nanodiamonds can also be internalised by other receptormediated pathways.…”
Section: Bio-compatibility Of Nanodiamondmentioning
confidence: 81%
“…cancer cells by identifying the sp 3 carbon Raman signals of NDs. 146 Growth hormone-ND complexes were created by carboxylating and covalently linking 100 nm NDs to the growth hormone. 146 When mapped by confocal Raman spectrophotometry, the NDs bound to growth hormone were located on the surface of cells, while the unconjugated carboxylated NDs were internalized into the cells.…”
Section: Elastic and Inelastic Light Scattering Imagingmentioning
confidence: 99%